Everybody was so young Gerald and Sara Murphy - a lost generation love story - Vaill, Amanda (Houghton Mifflin, 1998)
"There was a shine to life wherever they were," said Archibald MacLeish, describing his friends Gerald and Sara Murphy. The real-life models for Nicole and Dick Diver in F. Scott Fitzgerald's Tender Is the Night, the Murphys have appeared in virtually every book about the Lost Generation, for their apartment in Paris and their Mediterranean Villa America were the center of social and artistic life for the likes of Fitzgerald, Hemingway, Dorothy Parker, Stravinsky, John Dos Passos, Jean Cocteau, Cole Porter, and others. Gerald Murphy, the organizer of magical parties, was a brilliant painter whose work is currently undergoing a serious revival. Sara Murphy, an heiress who wore her pearls to the beach, was an enigmatic beauty whose allure enthralled Picasso (he painted her many times) as well as Fitzgerald and Hemingway.
Keywords: Murphy, Gerald <1888-1964>; Murphy, Sara; Murphy, Gerald -- 1888-1964; Murphy, Sara -- 1883-1975; Expatriate painters -- France -- Biography; Painters -- United States -- Biography; Painters' spouses -- United States -- Biography; Frankreich; USA; Biografie